ABOUT ONE ARTISTIC DEVICE OF GAFUR GULYAM - Nasiba Bozorova (Journal Park Publishing, 2024)
The article talks about the artistic technique used in Gafur Gulyam’s story “The Mischievous Man”. Using the example of the characters in the story, the views of the academic writer on socio-political life and era are analyzed. Changes in the human psyche and the occurrence of mental disorders as a result of pressure, violence, political pressure, as well as betrayal of loved ones, negative attitudes of surrounding people are revealed when studying the “history of madmen” in the work.
Keywords: Gafur Gulyam, irony, artistic technique, Uzbek literature, image, spiritual freedom, skill.